Imaging a concussion and the ensuing immune response at the blood–brain barrier - Rita H. Nguyen; Michelle Newton; Rachel M. Kratofil; Brittney N.V. Scott; Fernanda Castanheira; Jung-seok Kim; Florent Ginhoux; Steffen Jung; Paul Kubes (Proceedings of the National Academy of Sciences, 2025)
Concussions can cause debilitating symptoms despite no evidence of structural changes on diagnostic imaging. The cellular events occurring in the brain parenchyma following concussion, especially repetitive concussion, are not well elucidated. We developed a concussion model to induce a confined area of injury without causing frank hemorrhage. Using intravital microscopy, we observe activation of the vasculature that supported neutrophil rolling and platelet adhesion but no overt cellular recruitment from blood into brain parenchyma. Activated resident, not monocyte-derived, macrophages relocated to the injury site via Cx3cr1 and phagocytosed dysfunctional/detached astrocytes via scavenger receptors and TLR4, particularly after repetitive concussion. Additionally, microglia sealed areas of blood–brain barrier (BBB) disruption via purinergic pathways. Using a splitCre approach to dissect microglia and perivascular macrophages, we show that microglial invasion into the injury site is key to reducing BBB disruption. Our data suggest that microglia repair the BBB following concussion, but in doing so significantly alter the cellular ultrastructure of the brain milieu.